2015
DOI: 10.1093/molbev/msv236
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution Is Substantially Impeded by Hill–Robertson Interference inDrosophila

Abstract: Hill–Robertson interference (HRi) is expected to reduce the efficiency of natural selection when two or more linked selected sites do not segregate freely, but no attempt has been done so far to quantify the overall impact of HRi on the rate of adaptive evolution for any given genome. In this work, we estimate how much HRi impedes the rate of adaptive evolution in the coding genome of Drosophila melanogaster. We compiled a data set of 6,141 autosomal protein-coding genes from Drosophila, from which polymorphis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 76 publications
(99 reference statements)
7
67
0
Order By: Relevance
“…Among the 807 TEs located in regions with high recombination rates, 215 were fixed and 177 were present at low frequencies (LowFreq), defined here as being present at ≤ 10% frequency in each of the analyzed samples (Fig 2). Note that the percentage of fixed TEs in high recombination regions is significantly lower than the percentage in low recombination regions (27% vs 79% respectively, Chi-squared p-value = 2.2 e-16 ), as expected if the efficiency of selection is lower in low recombination regions, and slightly deleterious TEs reached fixation neutrally [37, 38]. Finally, 300 of the 807 TEs located in high recombination regions were present at high frequencies (HighFreq), defined here as being present at < 95% frequency overall and at >10% frequency in at least three samples (Fig 2, S1 Fig).…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Among the 807 TEs located in regions with high recombination rates, 215 were fixed and 177 were present at low frequencies (LowFreq), defined here as being present at ≤ 10% frequency in each of the analyzed samples (Fig 2). Note that the percentage of fixed TEs in high recombination regions is significantly lower than the percentage in low recombination regions (27% vs 79% respectively, Chi-squared p-value = 2.2 e-16 ), as expected if the efficiency of selection is lower in low recombination regions, and slightly deleterious TEs reached fixation neutrally [37, 38]. Finally, 300 of the 807 TEs located in high recombination regions were present at high frequencies (HighFreq), defined here as being present at < 95% frequency overall and at >10% frequency in at least three samples (Fig 2, S1 Fig).…”
Section: Resultsmentioning
confidence: 56%
“…In addition, among all the TEs present at high frequencies, TEs located in regions with high recombination rates are less likely to have increased in frequency neutrally compared with TEs located in low recombination regions. This is so because the efficiency of selection in genomic regions with low recombination rates tends to be lower due to the increase in noise generated by linked selection such as background selection and recurrent selective sweeps [37, 38]. Moreover, TEs located in low recombination regions are more likely to be linked to an adaptive mutation rather than being the causal mutation [33-35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes that are involved in highly conserved functions, such as developmental patterning and morphogenesis, are expected to be highly constrained [ 61 ]. Instead, altering the expression of crucial developmental genes through chromatin modifications or changes in transcription factor binding activity is a safer, yet effective way to control phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since N e for a genomic region is positively related to the rate of recombination [ 20 ], increased rates of fixation of advantageous mutations and decreased rates of fixation of deleterious mutations are expected in high recombination regions. Campos et al also observed that the rate of recombination is positively correlated with ω a , the estimated rate of advantageous substitution relative to the rate of neutral substitution (Box 1), suggesting that beneficial substitutions increase with increasing recombination rate, perhaps due to decreasing interference between selected loci [ 21 ].…”
Section: Empirical Findings From Applying the Mk Test And Its Derivatmentioning
confidence: 99%